2008
DOI: 10.1124/jpet.108.142091
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Down-Regulation of Intestinal and Hepatic Cytochrome P450 3A to Increased Absorption of Cyclosporine A in a Rat Nephrosis Model

Abstract: This study examined the contribution of changes in regulation of intestinal and hepatic cytochrome P450 3A (CYP3A) and multidrug resistance transporter 1 (Mdr1) to absorption of cyclosporine A (CsA) in a rat nephrosis model. Interleukin (IL)-6 was also measured. Puromycin aminonucleoside at a dose of 20 mg/100 g was administered intravenously. Tissue samples were dissected out from the upper and middle intestines and liver after development of nephrosis to measure the expression levels of mRNA and protein. CsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have shown that CYP3A gene expression can be down-regulated by chemotherapeutic substances [30,31] . Recently, transcriptional control of CYP3A enzymes has been linked to a group of nuclear receptors, which are responsible for a variety of processes, including xenobiotic metabolism [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CYP3A gene expression can be down-regulated by chemotherapeutic substances [30,31] . Recently, transcriptional control of CYP3A enzymes has been linked to a group of nuclear receptors, which are responsible for a variety of processes, including xenobiotic metabolism [32] .…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in 1 -OH-MDZ production was observed (p < 0.05), when the concentration of Cremophor RH40 was increased from 0.05% to 3% w/v. Studies have revealed that chemotherapeutic substances can downregulate the CYP3A gene expression [79,80]. Therefore, Western blot analysis was performed to examine the effect of SMEDDS on the CYP3A activity.…”
Section: Surfactantsmentioning
confidence: 99%